Writing and publishing for early career academics - Sunny L. Munn; Jill Zarestky; Jeremy Bohonos; Joshua Collins; Tonette Rocco (Adult Education Research Conference, 2021)
This panel will describe strategies to help early career academics prepare a first publication and develop a research agenda. This interactive session provides graduate students and early career scholars with an overview of the types of papers frequently found in academic journals, and shares approaches to writing for both peer-reviewed and non-peer-reviewed sections. The panel includes engaging participants in discussion around current research topics, drafting a manuscript, and building and executing a research agenda. The strategies and insights we share will be particularly useful to those wanting to understand the academic publishing process more thoroughly.
Keywords: Writing; publication; research; journal